Preservice elementary teachers' critique of instructional materials for science - Davis, Elizabeth A. (Science Education, 2006)
Science teachers must adapt curriculum materials, so preservice teachers must develop beginning proficiency with this authentic task of teaching. What criteria do they use when they critique these materials in preparation for adapting them, when they develop the criteria themselves and when they are given a set of criteria from which to choose? These results indicate that the 20 participating preservice elementary teachers held a sophisticated set of criteria for critiquing instructional materials; for example, they paid attention to scientific inquiry and instructional goals. In some cases, providing options from which they could select as a part of the instructional approach taken in the class allowed the preservice teachers to engage in substantive critique of the instructional materials along criteria not prominent in their initial set. Even with explicit support, however, the preservice teachers did not engage in substantive critique about how scientific content is represented. Furthermore, they typically describe inquiry as important to incorporate to promote student interest, not to engage students in genuine scientific activity. It is concluded that critique activities used in science methods courses should be authentic and scaffolded to be optimally effective. Critique along especially challenging dimensions needs systematic, explicit, and perhaps more consistent support. © 2006 Wiley Periodicals, Inc. Sci Ed90:348–375, 2006